ELT techniques and their influence on the listening skills in tenth grade EGB students at Unidad Educativa Academia Naval Almirante Illingworth, school year 2019-2020 - Narváez Fernández, Miguel Sebastián (2021)
The learning of English language for students is really difficult for students. When they are taught in school about English language they need to improve in the four skills of the English which are, speaking, grammar, writing, reading and listening being the most difficult skill to master for many students. The students will try to develop their listening comprehension with the methods taught by the teacher. This research start with the premise that ELT techniques can enhance the listening comprehension in students with the use of listening exercises based on those techniques. It gives students the context of how to listen depending on the situation. This will develop their cognitive capacity and listening skills. The first chapter of this research discusses the background of the problem by mentioning broad and specific objectives; it also details the population and sample involved in the study. The second chapter, the theoretical framework of this study is introduced that serve the function of explaining the different techniques and methods that can be used to help students in their listening skills. The third chapter of the study mentions the instruments analysis of the classroom utilized. And last the fourth chapter the readers will be able to see the different activities and techniques applied on the classroom for the students………..